Demand Theory Reconsidered - Morgenstern, Oskar (Quarterly Journal of Economics, 1948)
Introduction: scope of the paper, 165. — I. Individual demand schedules: fundamental properties, 166; alternative maximum bids, 168; reconstitution of the demand curve, 170; the reaction function, 172. — II. Collective demand schedules: additivity in closed markets, 175; more complex cases and the theory of games, 179; successive adaptation and time intervals, 182; recontracting, 185; successive adaptation in open markets, 186; further properties, non-additivity, 189. — III. Applications: elasticity of demand, 191; monopolistic discrimination and monopolistic competition, 195; the cobweb theorem, 198; the supply curve, non-additivity, 199. — Conclusions, 200.